2006
DOI: 10.1080/02640410500497667
|View full text |Cite
|
Sign up to set email alerts
|

The role of effort in moderating the anxiety – performance relationship: Testing the prediction of processing efficiency theory in simulated rally driving

Abstract: We tested some of the key predictions of processing efficiency theory using a simulated rally driving task. Two groups of participants were classified as either dispositionally high or low anxious based on trait anxiety scores and trained on a simulated driving task. Participants then raced individually on two similar courses under counterbalanced experimental conditions designed to manipulate the level of anxiety experienced. The effort exerted on the driving tasks was assessed though self-report (RSME), psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
47
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 32 publications
10
47
1
1
Order By: Relevance
“…Findings for the effect of anxiety on mental effort support previous work (e.g., Causer et al, 2011;Wilson et al, 2009aWilson et al, , 2009b, and provide further evidence to highlight the moderating role of effort under HA conditions (Wilson, Smith, Chattington, Ford, & Marple-Horvat, 2006). The effort compensating process seems to be necessary to prevent performance dropping below a certain ‫ء‬ p Ͻ .05, ‫ءء‬ p Ͻ .01.…”
Section: Discussionsupporting
confidence: 77%
“…Findings for the effect of anxiety on mental effort support previous work (e.g., Causer et al, 2011;Wilson et al, 2009aWilson et al, , 2009b, and provide further evidence to highlight the moderating role of effort under HA conditions (Wilson, Smith, Chattington, Ford, & Marple-Horvat, 2006). The effort compensating process seems to be necessary to prevent performance dropping below a certain ‫ء‬ p Ͻ .05, ‫ءء‬ p Ͻ .01.…”
Section: Discussionsupporting
confidence: 77%
“…Simulator research should attempt to discover this in future research. Alternatively, it may be interesting to see if trait interacts with state anxiety in simulator research; the majority of research has found significant changes in driving behaviour as a function of state anxiety (Briggs, Hole & Land, 2011;Morton & White, 2013;Wilson et al, 2006), and it is possible that trait anxiety may have an effect on this.…”
Section: Implications and Recommendations For Future Researchmentioning
confidence: 99%
“…The effects of increased anxiety on task goals and performance have been investigated, with findings suggesting that increased anxiety introduces task-irrelevant goals which compete with task-relevant goals, depleting CE resources (Lavric, Rippon, & Gray, 2003). This increase in overall workload, in turn, contributes to failures in spatial working memory (Shackman et al, 2006) and decreased visual awareness (Wilson, Smith, Chattington, Ford, & Marple-Horvat, 2006; See also Matthews, Bryant, Webb, & Harbluk, 2001;. Easterbrook (1959) was amongst the first to propose that emotional arousal reduces the range of visual cues that are used by an individual when scanning a visual scene.…”
Section: Introductionmentioning
confidence: 99%